2011
DOI: 10.1103/physrevb.83.113405
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spin-polarized quantum well states and spin-split energy dispersions of Co ultrathin films grown on Mo(110)

Abstract: Co thin films were epitaxially grown on Mo(110) and investigated by spinpolarized low-energy electron microscopy (SPLEEM). We find that the spin asymmetry of the electron reflectivity from the Co film alternates its sign as a function of both the electron energy and the Co film thickness as a result of spin polarized quantum well states in the Co film. By measuring spin dependent quantum well states, we are able to resolve the spin-split energy dispersions of the Co film precisely. The determined spin resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…To ascertain their origin, we examined the electronic states of Co films on Mo(110), which are isostructural to Co films on W(110) and magnetized, likewise, along the Co [1100] surface direction [32,33]. Mo (Z = 42) is much lighter than W (Z = 74) and has largely reduced spin-orbit effects [20].…”
Section: Resultsmentioning
confidence: 99%
“…To ascertain their origin, we examined the electronic states of Co films on Mo(110), which are isostructural to Co films on W(110) and magnetized, likewise, along the Co [1100] surface direction [32,33]. Mo (Z = 42) is much lighter than W (Z = 74) and has largely reduced spin-orbit effects [20].…”
Section: Resultsmentioning
confidence: 99%
“…While one might argue that quantum confinement is mostly associated with quasi-free (s-, p-like) electrons while magnetic properties are mostly determined by localized d electrons, the existence of d-QWSs has also recently been revealed [132,133], along with their influence on MAE of layered systems. For instance, thickness-dependent spin-split dispersions for Co thin films on Mo (110) have been measured [134]. Further experimental studies on ferromagnetic Fe [135] and Co [136] films show an oscillatory uniaxial anisotropy having a period of a few monolayers.…”
Section: Tuning Magnetic Properties Of Thin Films With External Elect...mentioning
confidence: 98%
“…It was shown that even for closely matched materials (Ag and Au), a reflectivity of few percent leads to observable effects of electron confinement. 3,4 Microscopic methods, such as scanning tunneling spectroscopy 5,6 and low-energy electron microscopy, 7 can reveal the presence of discrete QW states in films of reduced lateral dimensions (a few tens of nanometers) with limited momentum resolution. Complementarily, angle-resolved photoemission spectroscopy (ARPES) provides high energy and momentum resolutions at once, but averages over few to hundreds of micrometers (mainly depending on the optical focusing of the photon beam).…”
Section: ■ Introductionmentioning
confidence: 99%